2021
DOI: 10.1097/ajp.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Outcomes From Inpatient Multidisciplinary Pain Management Programs?

Abstract: Objectives: Although inpatient multidisciplinary pain management programs (PMPs) are effective for chronic pain, not all patients benefit equally and there is limited evidence regarding predictors of outcome. This meta-analysis aimed to identify patient or program characteristics associated with outcomes from inpatient PMPs, and to examine the time course of effects following discharge.Materials and Methods: Medline, EBSCO, and Scopus were searched to identify articles reporting outcomes from inpatient multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 112 publications
1
6
0
Order By: Relevance
“…Chronic self-reported anxiety (i.e., present before the COVID-19 pandemic) was significantly more frequent in the PCC group compared with the control group, which is consistent with the identification of pre-infection psychiatric comorbidities as risk factors for PCC [ 22 , 23 , 39 ]. These data support the broader literature linking anxiety and depression with the occurrence or persistence of physical symptoms [ 17 20 ], thus suggesting possible causal pathways and shared vulnerability factors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Chronic self-reported anxiety (i.e., present before the COVID-19 pandemic) was significantly more frequent in the PCC group compared with the control group, which is consistent with the identification of pre-infection psychiatric comorbidities as risk factors for PCC [ 22 , 23 , 39 ]. These data support the broader literature linking anxiety and depression with the occurrence or persistence of physical symptoms [ 17 20 ], thus suggesting possible causal pathways and shared vulnerability factors.…”
Section: Discussionsupporting
confidence: 86%
“…At the same time, the prevalence of anxiety and depressive symptoms and disorders substantially increased between the pre-and mid-pandemic periods in the general population [9,10] and more intensely in people with COVID-19 [11][12][13][14][15][16]. It has been suggested that anxiety and depression may play a role in the persistence of certain physical symptoms such as fatigue, sleep disorders, digestive disorders, and pain [17][18][19][20]. Indeed, a pre-infection diagnosis of anxiety or depression is a risk factor for persistent symptoms following SARS-CoV-2 infection [21][22][23], and depression at 1 month of SARS-CoV-2 infection is associated with an increased risk of persistent physical symptoms at 3 months, including pain and dyspnea [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Poulsen et al 23 indicated that pain catastrophizing does not have a predictive role in the outcome of pain relief in spinal cord stimulation for chronic neuropathic pain. Yet, most studies do indicate pain catastrophizing as a predictor of pain outcomes such as pain intensity, 24–29 just like the presence of depression and anxiety at baseline are seen as predictors of worse pain outcome 9,26–30 . The results of this study suggest that although high pain severity and psychological values were present, complex cases do not respond differently in pain intensity.…”
Section: Discussionmentioning
confidence: 52%
“…Yet, most studies do indicate pain catastrophizing as a predictor of pain outcomes such as pain intensity, [24][25][26][27][28][29] just like the presence of depression and anxiety at baseline are seen as predictors of worse pain outcome. 9,[26][27][28][29][30] The results of this study suggest that although high pain severity and psychological values were present, complex cases do not respond differently in pain intensity. However, in our recent study on drug and interventional RCT's and the DATAPAIN registry cohort, greater pain relief at follow-up was found at follow-up in patients with severe pain (≥ 7 on the NRS) 31,32 The finding of a similar pain relief in both groups may suggest that the cluster of cognitive-affective, psychological factors and pain severity reduces the pain relief because a greater reduction in pain intensity could theoretically be obtained in patients with a high pain score at baseline.…”
Section: Primary Outcomesmentioning
confidence: 59%
“… 4 , 5 , 34 , 37 Moreover, a recent systematic review concluded that higher pain intensity and longer pain duration were associated with larger effect sizes for several IPRP outcomes. 38 As this study examines real-world data and as previous real-world studies have shown that a more severe clinical picture is associated with better results, we hypothesize that the baseline values of pain intensity and psychological distress would show positive associations with the three outcomes ( Figure 1 ).…”
Section: Our Path Model – Overall Hypothesismentioning
confidence: 84%